ANALISIS DETERMINAN DISIPLIN KERJA PEGAWAI PADA UPT PUSAT IPTEK DAN BAHASA KOTA PONTIANAK - Sulaiman; Lhery Swara Oktaf Adania; M Awaluddin (JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI PONTIANAK, 2023)
This research began with the problems related to whether employee take home paid and fingerprint attendance affect the work discipline of the employees of the Office of Investment and One Stop Service, West Kalimantan. Current study is aimed at investigation the impact of employee take home paid and fingerprint attendance on employee working discipline at the Office of Investment and One Stop Service, West Kalimantan Province. Current research is quantitative method approach with descriptive analysis. The sample used in this study amounted to 48 respondents. The data collection technique used a questionnaire with a measurement scale using a Likert scale. Based on the T test and F test, employee take home paid (X1) has a partial effect and fingerprint attendance (X2) has a partial effect. And have a simultaneously affect on employee working discipline (Y). And based on the coefficient of determination, additional employee income and fingerprint attendance influenced about 77.8% on employee work discipline at the UPT Center for Science and Language Pontianak City,, while the other 22.2% were influenced by other factors not examined in this study.